Alteration of DNA Damage Response Causes Cleft Palate - Yamaguchi, Hiroyuki; Kitami, Kohei; Wu, Xiao; He, Li; Wang, Jianbo; Wang, Bin; Komatsu, Yoshihiro (Frontiers in Physiology, 2021)
Cleft palate is one of the most common craniofacial birth defects. However, little is known how changes in the DNA damage response (DDR) cause cleft palate. To determine the role of DDR during palatogenesis, the DDR process was altered using a pharmacological intervention approach. A compromised DDR caused by a polyADP-ribose polymerase (PARP) enzyme inhibitor resulted in cleft palate in wild-type mouse embryos, with increased DNA damage and apoptosis. In addition, a mouse genetic approach was employed to disrupt BRCA1 and BRCA2, known as key players in DDR. An ectomesenchymal-specific deletion of Brca1 or Brca2 resulted in cleft palate due to attenuation of cell survival. This was supported by the phenotypes of the ectomesenchymal-specific Brca1/Brca2 double-knockout mice. The cleft palate phenotype was rescued by superimposing p53 null alleles, demonstrating that BRCA1/2–p53 DDR pathway is critical for palatogenesis. Our study highlights the importance of DDR in palatogenesis.